Deciphering UV‐induced DNA Damage Responses to Prevent and Treat Skin Cancer. (4th May 2020) - Lee, Jihoon W.; Ratnakumar, Kajan; Hung, Kai‐Feng; Rokunohe, Daiki; Kawasumi, Masaoki
Abstract: Ultraviolet (UV) radiation is among the most prevalent environmental factors that influence human health and disease. Even 1 h of UV irradiation extensively damages the genome. To cope with resulting deleterious DNA lesions, cells activate a multitude of DNA damage response pathways, including DNA repair. Strikingly, UV‐induced DNA damage formation and repair are affected by chromatin state. When cells enter S phase with these lesions, a distinct mutation signature is created via error‐prone translesion synthesis. Chronic UV exposure leads to high mutation burden in skin and consequently the development of skin cancer, the most common cancer in the United States. Intriguingly, UV‐induced oxidative stress has opposing effects on carcinogenesis. Elucidating the molecular mechanisms of UV‐induced DNA damage responses will be useful for preventing and treating skin cancer with greater precision. Excitingly, recent studies have uncovered substantial depth of novel findings regarding the molecular and cellular consequences of UV irradiation. In this review, we will discuss updated mechanisms of UV‐induced DNA damage responses including the ATR pathway, which maintains genome integrity following UV irradiation. We will also present current strategies for preventing and treating nonmelanoma skin cancer, including ATR pathway inhibition for prevention and photodynamic therapy for treatment. Abstract : Ultraviolet (UV) radiation is an extremely prevalent environmental factor that extensively damages the genome. Cells respond to UV‐induced DNA damage by activating multiple biological processes: DNA damage checkpoint for cell cycle arrest, DNA repair that is affected by chromatin state, and DNA damage tolerance that may promote survival with mutations. Chronic UV exposure increases mutation burden, leading to skin cancer development. This process is facilitated by reactive oxygen species (ROS), inflammation and immunosuppression. Recent studies have elucidated precise molecular and cellular consequences of UV irradiation. Targeting UV‐induced DNA damage responses is an effective means to prevent and treat skin cancer.